Application of Shumann and Joosten classification in fen peatland degradation stage assessment – A case study from southern Poland - Glina, Bartłomiej; Kołodziejczyk-Prażmo, Katarzyna; Bogacz, Adam; Tomaszewska, Klara; Kaczmarek, Zbigniew; Gajewskl, Piotr (Ecological Questions, 2017)
The aim of this paper was to assess the degradation stage of fen peatland located in the north-western part of the Opolskie voivodeship in accordance with “peatland degradation stages” classification. Understanding of the current state of peatland will be helpful in the future management and possible restoration. Field survey including vegetation and soil research were carried out in May 2013, soil material for laboratory analysis were collected by using “Instorf” peat sampler from four sampling points. Obtained results allowed to classify the study area (located within a larger peatland complex along the Prosna river valley) to minor stage of degrada- tion, with spontaneous changes in vegetation community and soil cover. Only few species of plants typical for fen peatlands were recorded. Moreover, soil cover research did not confirm mursh forming process, typical for strongly degraded peatland areas. Obtained results may indicate that possible future restoration will bring the expected effect. It is very likely, that fen peatland vegetation will regenerate spontaneously, provided that diaspores of the key peat-forming plant species are available in the soil.